Peran Influencer, Fitur Live Streaming dan Electronic Word Of Mouth Terhadap Keputusan Pembelian Produk Skincare The Originote pada Aplikasi Tik Tok - Usman, Dhea Monicha; Hariasih, Misti; Pebrianggara, Alshaf (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Tik Tok application has become one of the most popular digital media that is widely used by entrepreneurs as an online shopping platform and has around 99.1 million users in Indonesia in 2021, with an average of 68% female users and 32% male users. This research aims to examine the role of influencers, live streaming features and electronic word of mouth on purchasing decisions for The Originote skincare products on the Tik Tok application. With an unknown population, the Lemeshow formula is used to calculate the sample size, with 100 respondents. This research is quantitative and uses the Smart PLS analysis tool. The research results show that Influencers have a significant positive effect on Purchasing Decisions, the Live Streaming Feature has a significant positive effect on Purchasing Decisions and Electronic Word of Mouth has no effect on Purchasing Decisions for The Originote Skincare Products on the Tik Tok Application.